Kristus Sebagai Jalan Pendamaian: Studi Kata hilasterion Sesuai Struktur Gramatikal dan Leksikal dalam Roma 3:25 - Andreas Danang Rusmiyanto; Rofer Ourano Michael Tendean (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2022)
Paul's letter to the Romans is known for its in-depth doctrinal discussion, one of which is the teaching of salvation in Jesus Christ. In Romans 3:25, Paul says that Christ is the “way of atonement,” which comes from the word ἱλαστήριον (hilasterion). This word refers to the closing of the ark of the covenant in the Most Holy. Therefore, this research aims to conduct a more in-depth word study by looking at the grammatical and lexical structure of the word to see what Paul means by using this word. As a result: the use of the word hilasterion is a typology that refers to the Day of Atonement in Leviticus 16. Lexically, the word hilasterion refers to the lid of the ark of the old covenant, which was sprinkled with the blood of the atoning sacrifice on the annual day of penance. While grammatically, it states that Jesus is